Three new records of polyporoid mushrooms from Himachal Pradesh (India) - Kumar, Hardesh; Singh, Avneet Pal; Bansal, Gulshan (Mushroom Research, 2024)
In this paper an account of three polyporoid mushrooms viz. Bresadolia cuticulata (Y.C. Dai, Jing Si & Schigel) Audet, Ganoderma fulvellum Bres., and Tyromyces fissilis (Berk. & M.A Curtis) Donk, has been given. Of these, Bresadolia cuticulata and Tyromyces fissilis are described for the first time from India while Ganoderma fulvellum in new for Himachal Pradesh.